Effect of Nitrogen and Potassium on Early Growth of Jatropha (Jatropha curcas) - Bustanul Arifin (Central Research Institute For Agriculture, 2022)
Jatropha curcas is a plant from the Euphorbiaceae family which has the potential for medicinal plants and as a renewable energy source. The production and process of seed and fruit formation is highly dependent on environmental genetic factors, agronomy and the interaction between these factors. The quality of the initial growth of the plant is one of the factors that determine the level of production of Jatropha. The aim of this study was to determine the effect of different levels of N and K fertilizer on the initial growth of Jatropha curcas and to obtain the optimal dose. The hypothesis put forward is that there is an interaction of N and K between the application of nitrogen fertilizers and potassium fertilizers on the initial growth of jatropha and rapid growth of jatropha is obtained by providing the highest levels of N and K. The results showed that N application of 40 kg N/ha and without K had the best effect on the initial growth of jatropha compared to other treatments. Meanwhile, the addition of N and K levels had an effect on decreasing the growth of jatropha even though the total N and K content of leaves was high, because high levels of N and K fertilization caused poisoning and salt stress in plants due to the very high status of K content in the soil.